Mesenteric Lymph Node Recurrence of a Primary Colorectal Leiomyosarcoma - Amélie Beauchamp; Roy Hajjar; Sharmila Khullar; Mathieu Latour; Frank Schwenter; Herawaty Sebajang (Case Reports in Surgery)
Primary colorectal leiomyosarcoma is an excessively rare entity. It is associated with an aggressive behavior and typically favor hematogenous spread. The current standard of care is surgical resection. A 49-year-old patient presented with a 2-month history of fever. A PET-scan revealed a hypermetabolic mass in the transverse colon, and colonoscopy confirmed a tumor. A right hemicolectomy was performed. Histopathological diagnosis was of a leiomyosarcoma. Fourteen months after the surgery, a follow-up abdominal scan revealed a 2 cm mesenteric lymph node that was hypermetabolic on PET-scan. The mesenteric lymph node was resected and histopathology confirmed a leiomyosarcoma metastasis. This case opens the controversy on the management of rare lymph node recurrences in colorectal leiomyosarcoma.